Materiality and Trajectories of a Lima Middle-Class Neighborhood: Architectural Design as Cultural Phenomenon in a Context of Truncated Modernity - Acha Kutscher, Elisabeth (2025)
From an interdisciplinary perspective, this work explores the meanings, conditions and possibilities of a new type of architecture that emerged in the 1950s, through two residences located in the Aurora urbanization (hereafter La Aurora), a Lima middle-class neighborhood. The referent of the avant-garde artist at that time, of which architecture formed an explicit part, resided in the capacity to appropriate the diversity of traditions and their intersection with technological modernization, giving rise to a new episteme. It is postulated that both constructions chosen in this study express a genuine expressive potential of an original and authentic artistic-national architecture that has been surpassed by the phallic city and a capitalist logic that tends to standardize and limit ludic enjoyment in ways of inhabiting. The findings of this research reveal a known but insufficiently studied reality: unveiling unsuspected meanings of the becoming of the experience of inhabiting a dwelling with a particular architectural design. This concerns, in this case, an educated middle-class sector that was capable of moving with fluidity and creative skill among the different stages of the country's history and cultural traditions, without abandoning a fruitful dialogue with European avant-gardes.